Technical Writing: A Practical Approach - Pfeiffer, William S. (Upper Saddle River Prentice-Hall, Inc., 1997)
For people who are planning on working in business or industry, it is important to know the art of technical writing. Will help with increasing your writing skills and making career advancement a possibility.
Keywords: Writing